Penerapan Pendidikan Multikultural dalam Interaksi Santri di Pondok Pesantren Tahfizil Qur`an - Moh. Syahrulloh (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
In creating a conducive social climate, communication between individuals is certainly very necessary as a means to understand one person another. The students at the Tahfizil Qur`a>n Darul Muhajirin Islamic Boarding School in Gedangsewu Pare Kediri are those who live and study at the Tahfizil Qur`a>n Darul Muhajirin Islamic Boarding School with backgrounds from different families and regions, some of whom from East Java, Central Java, Sumatra, who have their own regional languages. The atmosphere of education is no different from most other educations, but what is certain is that the large number of students studying in Islamic boarding schools always creates new problems. This is understandable due to the dynamics of the life of the existing students. The approach in this study is a qualitative research model, which is an approach to conducting research that is oriented toward natural phenomena or symptoms with the provision of theories to obtain various interpretive descriptions according to logical and rational scientific research principles on the data collected. The results of the research discussion concluded as follows: Pondok Pesantren Tahfizil Qur`a>n Darul Muhajirin Gedangsewu Pare has implemented multicultural education in the interaction of students; the practice is found in the design of the students' rooms that are not compartmentalized, the procession of sitting students during the recitation of the yellow book individually. Lesehan or all sitting on benches when studying, discussion opportunities during deliberation, recitation of the yellow book or when sorogan al-Qur'an, Social service in the form of ro`an or activities with the community, Culture of queuing such as when taking food, memorizing deposits to the ustadz , bathing, competitions between students which are held towards the end of the school year. Later, IHDAM alumni huffadz routines were also found. While the student interaction model is an associative model consisting of cooperation in the form of harmony and mutual assistance, a form of bargaining, a form of co-optation, a form of coalition, accommodation in the form of coercion, compromise, arbitration, mediation, consultation, and tolerance. There are dissociative models in the form of competition, contravention and conflict.